Uwagi o statusie jednostki przyimkowej - Lachur, Czesław (Studia Rossica Posnaniensia, 2010)
One of primary tasks within recently intensified research on Slavic prepositions is compiling a full corpus of units that can function as prepositions in specific circumstances, and their versatile characteristics in the particular Slavic languages. This paper is yet another contribution to studies on the Polish component of the Slavic system of secondary prepositions